Progress in research on ultraviolet disinfection technology for inhibiting pathogen transmission in built environment - Jie ZHAO; Lei ZHAO; Jinhui WU; Ying YI; Cheng DENG; Jiancheng QI; Yucheng SUN; Zongxing ZHANG (Editorial Office of Chinese Journal of Public Health, 2023)
Ultraviolet (UV) irradiation is an effective and broad-spectrum disinfection method. Conventional mercury vapor UV lamps are inexpensive and have been used most commonly, but there are shortcomings such as low irradiation, long disinfection cycle, and the generation of ozone. In recent years, the emerging UV disinfection technologies have shown great potential, thus domestic and international research institutions have conducted a number of studies on UV disinfection. In this review, we summarized the mechanism of UV damage to nucleic acids and proteins. Further, the effects of temperature, humidity and different media on UV disinfection technology were analyzed. Moreover, the safety, development status and future research applications of UV irradiation were clarified.